Intervju med Manuel Stetter - Kaufman, Tone Stangeland (Tidsskrift for Praktisk Teologi, 2024)
This is an interview with professor in practical theology at the University of Rostock, Manuel Stetter, about his research on funeral practices. The interview is conducted by professor Tone Stangeland Kaufman, Oslo.